2016
DOI: 10.5021/ad.2016.28.2.210
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Collagen Tissue in Papular Elastorrhexis, Eruptive Collagenoma, and Nevus Anelasticus

Abstract: BackgroundPapular elastorrhexis (PE), eruptive collagenoma (EC), and nevus anelasticus (NA) are described as multiple small papules with decrease, fragmentation, or lack of dermal elastic fibers. These diseases are suggested to be the same entity. The change of collagen fibers in the conditions has not been addressed to date.ObjectiveWe compared the clinical features of the 3 diseases and investigated changes in the collagen fibers involved.MethodsTwenty-four cases of PE, 12 cases of EC, and 2 cases of NA foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…It should be noted that some cases labeled as “papular elastorrhexis” and “nevus anelasticus” show considerable clinical and histologic overlap with eruptive collagenomas, and may represent the same pathologic entity as eruptive collagenomas . Nevus anelasticus is described as “perifollicular papules” and papular elastorrhexis consists of multiple, acquired, 2‐5 mm, flat, firm, painless, oval‐shaped papules; like eruptive collagenoma, these two conditions are acquired most often in childhood and adolescence and affect the upper part of the body (torso and upper extremities).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that some cases labeled as “papular elastorrhexis” and “nevus anelasticus” show considerable clinical and histologic overlap with eruptive collagenomas, and may represent the same pathologic entity as eruptive collagenomas . Nevus anelasticus is described as “perifollicular papules” and papular elastorrhexis consists of multiple, acquired, 2‐5 mm, flat, firm, painless, oval‐shaped papules; like eruptive collagenoma, these two conditions are acquired most often in childhood and adolescence and affect the upper part of the body (torso and upper extremities).…”
Section: Discussionmentioning
confidence: 99%
“…Nevus anelasticus is described as “perifollicular papules” and papular elastorrhexis consists of multiple, acquired, 2‐5 mm, flat, firm, painless, oval‐shaped papules; like eruptive collagenoma, these two conditions are acquired most often in childhood and adolescence and affect the upper part of the body (torso and upper extremities). Ryder and Antaya and Lee and Sung compare these three conditions, and conclude that “nevus anelasticus, papular elastorrhexis, and eruptive collagenoma are the same entity.” Other authors have also proposed that eruptive collagenoma and papular elastorrhexis are one and the same condition. Lesions resembling eruptive collagenoma both clinically and histopathologically, but arising on the neck in older individuals, have been labeled as “white fibrous papulosis of the neck.” The relationship between this condition and EC is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Nevus anelasticus and eruptive collagenoma are difficult to distinguish from papular elastorrhexis clinically and histopathologically. In fact, it is suggested that papular elastorrhexis, nevus anelasticus, and eruptive collagenoma might be the same entity and be named “eruptive papular collageno‐elastopathy” or “papular collagenoma” . The fine collagen fibers are common, although various histological features in collagen fibers which are classified into normal, fine, and thick collagen groups have been reported .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is suggested that papular elastorrhexis, nevus anelasticus, and eruptive collagenoma might be the same entity and be named “eruptive papular collageno‐elastopathy” or “papular collagenoma” . The fine collagen fibers are common, although various histological features in collagen fibers which are classified into normal, fine, and thick collagen groups have been reported . In a case diagnosed as eruptive collagenoma where fine collagen fibers were observed, electron microscopy showed that the collagen fibers were sparse and loose and did not form bundles adequately …”
Section: Discussionmentioning
confidence: 99%
“…In a research published in 2016, Seung et al evaluated the status of collagen tissue in eruptive collagenoma, nevus anelasticus and papular elastorrhexis. The selected cases were reclassified into three groups: normal collagen group; fine, dense collagen group; and thick, dense collagen group [ 19 ]. This study indicated that different kinds of collagen could be observed in collagenomas probably in accordance with different stages of the tumor.…”
Section: Discussionmentioning
confidence: 99%